Outcome of allogeneic hematopoietic stem cell transplantation for T-cell lymphoblastic leukemia/lymphoma: A single-center study. (September 2021) - Yasuda, Shunichiro; Najima, Yuho; Konishi, Tatsuya; Yamada, Yuta; Nagata, Akihito; Takezaki, Toshiaki; Kaito, Satoshi; Kurosawa, Shuhei; Sakaguchi, Masahiro; Harada, Kaito; Shingai, Naoki; Yoshioka, Kosuke; et al.
Highlights: Allo-HSCT outcomes for T-ALL/LBL and Ph-negative B-ALL were analyzed and compared. Allo-HSCT outcomes for T-ALL/LBL were comparable to those for Ph-negative B-ALL. Regardless of the disease entity, achieving CR at allo-HSCT could decrease relapse. Regardless of the disease entity, achieving CR at allo-HSCT leads to a favorable OS. Advances in treatment strategies before allo-HSCT can improve T-ALL/LBL outcomes. Abstract: Although the indications for allogeneic hematopoietic stem cell transplantation (allo-HSCT) as a treatment for T-cell acute lymphoblastic leukemia/lymphoma (T-ALL/LBL) and Philadelphia chromosome (Ph)-negative B-cell acute lymphoblastic leukemia (B-ALL) are similar, few studies have compared its outcomes for T-ALL/LBL and Ph-negative B-ALL. The clinical data of 28 patients with T-ALL, 16 with T-LBL, and 99 with Ph-negative B-ALL who underwent the first allo-HSCT from 2000 to 2019 were retrospectively analyzed. Complete remission (CR) rates at allo-HSCT were 79 %, 63 %, and 75 % for T-ALL, T-LBL, and B-ALL, respectively; the 3-year overall survival (OS) rates were 55.7 %, 56.2 %, and 58.6 %, respectively ( p = 0.92). Univariate analysis revealed that disease subtypes were not significantly associated with OS (B-ALL vs. T-ALL: hazard ratio [HR]=0.89, p = 0.70; T-LBL vs. T-ALL: HR=0.87, p = 0.75), and CR at allo-HSCT was the only prognostic factor for OS (HR=0.25, p < 0.001). Multivariate analysis demonstrated that CR at allo-HSCT was the only predictor of OS (HR=0.24, p < 0.001). In all three disease subtypes, patients in CR at allo-HSCT tended to have a lower cumulative incidence of relapse than did those in non-CR (T-ALL: 13.6 % vs. 50.0 %, p = 0.10; T-LBL: 20.0 % vs. 50.0 %, p = 0.21; B-ALL: 10.0 % vs. 56.0 %, p < 0.01). Thus, the outcomes of allo-HSCT for T-ALL/LBL were comparable to those of Ph-negative B-ALL. Irrespective of the disease subtypes, achieving CR before allo-HSCT was associated with a favorable OS. Further advances in chemotherapy before allo-HSCT and defining the optimal timing of allo-HSCT would improve the prognosis of patients with T-ALL/LBL.